Social Media and the Formation of Organizational Reputation - Etter, Michael; Ravasi, Davide; Colleoni, Elanor (Academy of Management Review, 2019)
The rise of social media is changing how evaluative judgments about organizations are produced and disseminated in the public domain. In this article we discuss how these changes question traditional assumptions that research on media reputation rests upon, and we offer an alternative framework that begins to account for how the more active role of audiences, the changing ways in which they express their evaluations, and the increasing heterogeneity and dynamism that characterize media reputation influence the formation of organizational reputations.